In vitro organogenesis in watermelon cotyledons - Krug, Maria Graziela Zagatto; Stipp, Liliane Cristina Libório; Rodriguez, Adriana Pinheiro Martinelli; Mendes, Beatriz Mendes Madalena Januzzi (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to study the in vitro organogenesis of Citrullus lanatus, by the induction of adventitious buds in cotyledon segments cultured in medium supplemented with cytokinin. Explants were collected from one, three and five-day-old in vitro germinated seedlings, considering the distal and proximal cotyledon regions. The data obtained showed that in vitro organogenesis of watermelon occurred with higher efficiency, when cotyledon segments from the proximal region collected from three-day-old seedlings were cultivated in medium MS, supplemented with BAP (1 mg L-l) and coconut water (10%). The histological study showed that the organogenesis occurs directly, without callus formation, on epidermal and subepidermal layers of the explants. Adventitious shoots were characterized by the development of shoot apical meristem and leaf primordia. The formation of protuberances, that do not develop into adventitious buds, was also observed.